The Effects of Cannabis Use during Pregnancy on Low Birth Weight and Preterm Birth: A Systematic Review and Meta-analysis - Baía, Inês; Domingues, Rosa M. S. M. (American Journal of Perinatology, 2022)
Objective Our objective was to summarize the literature regarding the effects of cannabis use during pregnancy on low birth weight (LBW), preterm birth (PTB), and small for gestational age (SGA).Study Design This is a systematic review and meta-analysis. A literature search was conducted in PubMed, Scopus, EBSCO, and Web of Science in May 2021 and updated in November 2021. Only studies that assessed the isolated use of cannabis during pregnancy, controlling for cigarette smoking, and other illicit drug use were included. Data were synthesized using a narrative summary and pooled adjusted estimates, and 95% confidence intervals (CIs) were calculated for each outcome. Data were analyzed using Stata 13.0 with METAN software package, using random effects. Statistical heterogeneity was assessed using Cochran's Q and Higgins I2 tests.Results In total, 32 studies were included with data from approximately 5.5 million women with the LBW outcome and 23 million with the PTB and SGA outcomes. Pregnant women using cannabis are at increased risk for LBW (adjusted odds ratio [aOR] = 1.52; 95% CI = [1.18; 1.96]), PTB (aOR = 1.39; 95% CI = [1.28; 1.51]), and SGA (aOR = 1.47; 95% CI = [1.38; 1.58]). Studies that assessed the type of PTB and gestational age at birth indicate higher risks of spontaneous PTB and of early or very-early PTBs associated with cannabis use during pregnancy. The few studies that assessed the timing and frequency of consumption suggest a dose–response effect, with higher odds of negative outcomes among women who reported heavy use and with continued use during the second and third trimesters of gestation.Conclusion There is an effect of cannabis irrespective of other illicit drugs and tobacco despite high heterogeneity and low quality of evidence. There is a need to discuss public policies regarding cannabis' regulation and how it influences its consumption. Future studies should focus on the effects of cannabis's type (medicinal or recreational), timing, and dosage during pregnancy on perinatal outcomes.Key Points
Keywords: cannabis; pregnancy; preterm birth; infant; low birth weight; infant; small for gestational age; systematic review; meta-analysis